"Foundations of Software Technology and Theoretical Computer Science: 17th Conference Kharagpur, India, December 18-20, 1997 Proceedings" - Ramesh (S) Ed.; Sivakumar (G) Ed. (1997)
Software Technology
Keywords: Software Technology